Students’ views and experiences of the philosophical inquiry method in learning ‘aqidah: a case study of form two students - Hamzah , Lina Mursyidah; Hussien, Suhailah; Wan Yusoff, Wan Mazwati (Association of Malay Muslim Intellectuals, 2015)
The aim of this study is to explore students’ views on the use of philosophical inquiry method in teaching ‘Aqidah. This qualitative study involved form -two students in an Islamic secondary school in Gombak, focusing on Islamic Education subject particularly in the component of ‘Aqidah. After completing the three philosophical inquiry sessions/classes, four students were interviewed to gauge their views and experiences of the sessions. Results from the research showed that students viewed the lessons as easyto understand. They also shared their experiences that the philosophical inquiry method has allowed them to explore learning beyond the textbook content. To this extent, it can be said that the philosophical inquiry method has given positive experiences in the teaching and learning of an Islamic classroom.